When do trade‐offs occur? The roles of energy constraints and trait flexibility in bushcricket populations. (23rd December 2017) - Barbosa, F.; Rebar, D.; Greenfield, M. D.
Abstract: In many animal species, the expression of sexually selected traits is negatively correlated with traits associated with survival such as immune function, a relationship termed a 'trade‐off'. But an alternative in which sexually selected traits are positively correlated with survival traits is also widespread. We propose that the nature of intertrait relationships is largely determined by overall energy expenditure, energy availability and trait flexibility, with trade‐offs expected when individuals are subject to energy constraints. We tested this hypothesis in Ephippiger diurnus, a European bushcricket in which males are distinguished by two prominent sexually selected traits, acoustic calls and a large spermatophore transferred to the female at mating, and where immune function may be critical in survival. Ephippiger diurnus are distributed as small, isolated populations that are differentiated genetically and behaviourally. We analysed songs, spermatophores and the immune function in male individuals from eight populations spanning a range of song types. As predicted, we only found trade‐offs in those populations that expended more energy on song and were less flexible in their ability to adjust that expenditure. Ultimately, energy constraints and resulting trade‐offs may limit the evolution of song exaggeration in E. diurnus populations broadcasting long calls comprised of multiple 'syllables'.